UTILIZATION OF THE WATER FOOTPRINT REGULATION CONCEPT AS AN INSTRUMENT FOR CONTROLLING INDUSTRIAL WATER CONSUMPTION IN PROTECTING WATER RESOURCES - Muhammad Ghazi Alfaruqi Ilmi; Hafidz Aulia Faturrahman; Nabilla Meisya Adriani (Catalist Indo Publisher, 2026)
This study aims to analyze the legal framework governing industrial water resource utilization in Indonesia and to examine the potential application of the water footprint concept as a legal instrument for controlling industrial water consumption in support of sustainable water resource protection. This research employs a normative legal research method using statutory, conceptual, and comparative approaches. Data were collected through a library study comprising primary, secondary, and tertiary legal materials and were analyzed qualitatively. The findings indicate that the regulation of water resource utilization in Indonesia has been governed under Law Number 17 of 2019 on Water Resources, Law Number 32 of 2009 on Environmental Protection and Management, and regulations concerning risk-based business licensing. However, these legal frameworks have not comprehensively accommodated mechanisms for measuring and controlling industrial water consumption. The water footprint concept, through the measurement of blue, green, and grey water footprints, offers significant potential to be integrated into the water resource management and licensing system through mechanisms of measurement, reporting, and monitoring of industrial water use. Therefore, integrating the water footprint concept into Indonesia's legal framework can serve as a preventive legal instrument to enhance water-use efficiency, strengthen water resource protection, and promote sustainable industrial development.